التشبيه في شعر سعيد الباكستاني: Simile in the Poetry of Saeed Al-Pakistani (Al-Aasar, 2025)
This study explores the use of simile in the poetry of Saeed Al-Pakistani, examining it through a rhetorical lens while taking into account his scholarly and literary background. Saeed Al-Pakistani is a contemporary poet whose life was marked by hardship, illness, and persistent struggle for knowledge. These experiences significantly shaped his poetic language and rhetorical choices. The research focuses on simile as one of the most prominent rhetorical devices in his poetry, analyzing its structures, types, and functions, and highlighting its aesthetic and semantic roles. The study adopts an analytical and descriptive methodology, drawing upon selected poetic texts to illustrate how simile functions as a tool for expressing emotional depth, spiritual reflection, and intellectual maturity. It demonstrates that Al-Pakistani’s similes are not merely ornamental but are deeply rooted in his lived experiences, religious education, and engagement with classical Arabic literature. His similes often draw from natural phenomena, religious imagery, and everyday life, creating vivid and accessible expressions that resonate with readers. Furthermore, the research situates Al-Pakistani’s poetic practice within the broader tradition of Arabic rhetoric (balāghah), showing his conscious or intuitive adherence to classical rhetorical principles while addressing contemporary concerns. By linking his rhetorical style to his biographical context, the study reveals how personal suffering and scholarly dedication can enrich poetic expression. Ultimately, this research contributes to the study of modern Arabic poetry by shedding light on an underexplored poet and demonstrating the enduring relevance of classical rhetorical devices in contemporary poetic discourse.